2007
DOI: 10.1038/sj.onc.1210464
|View full text |Cite
|
Sign up to set email alerts
|

KIT oncoprotein interactions in gastrointestinal stromal tumors: therapeutic relevance

Abstract: Most gastrointestinal stromal tumors (GISTs) express oncogenic and constitutively active forms of the KIT or platelet-derived growth factor receptor alpha (PDGFRA) receptor tyrosine kinase proteins, and these kinase oncoproteins serve as targets for effective therapies. Given that mutant KIT oncoproteins serve crucial transforming roles in GISTs, we evaluated interactions with the KIT oncoproteins and determined signaling pathways that are dependent on KIT oncogenic activation in GISTs. Tyrosine-phosphorylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 20 publications
4
40
0
Order By: Relevance
“…KIT activation is known to result in binding and activation of phosphatidylinositol-3-kinase (PI3-K) and phospholipase C-g, which regulate, respectively, membrane translocation of PKCy and synthesis of the PKCy cofactor diacylglycerol (Villalba et al, 2002;Altman and Villalba, 2003). Further, we have shown that KIT oncoproteins complex with and tyrosine phosphorylate PKCy in GISTs, and might thereby directly activate PKCy (Zhu et al, 2007). These observations suggest that KIT and PKCy participate in a positive feedback loop in GIST.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…KIT activation is known to result in binding and activation of phosphatidylinositol-3-kinase (PI3-K) and phospholipase C-g, which regulate, respectively, membrane translocation of PKCy and synthesis of the PKCy cofactor diacylglycerol (Villalba et al, 2002;Altman and Villalba, 2003). Further, we have shown that KIT oncoproteins complex with and tyrosine phosphorylate PKCy in GISTs, and might thereby directly activate PKCy (Zhu et al, 2007). These observations suggest that KIT and PKCy participate in a positive feedback loop in GIST.…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, KIT/ PDGFRA inhibition by small-molecule kinase inhibitors such as imatinib mesylate or sunitinib malate has become the mainstay of treatment in patients with inoperable GIST. At the same time, studies of human GIST cell lines and transgenic mouse models have enabled substantial advances in understanding the central roles of KIT/PDGFRA signaling pathways in GIST cell proliferation and survival (Demetri et al, 2002;Heinrich et al, 2003;Duensing et al, 2004b;Corless et al, 2005;Rossi et al, 2006;Bauer et al, 2007;Zhu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, this strategy could be used to maximize the effect of upstream kinase inhibitors or used in isolation. Notably, the PI3-kinase and MEK/MAPK pathways are strongly activated in most GISTs, and are partly dependent on KIT/PDGFRA activation (78,84,85). Recently, protein kinase C theta (PKCθ) has been identified as a novel therapeutic target in GIST.…”
Section: Strategies To Overcome And/or Prevent Resistancementioning
confidence: 99%
“…In GIST cell lines, KIT expression is PKCθ-dependent; RNAi knockdown of PKCθ decreases KIT gene transcription, and also decreases mutant KIT expression (87). Although the precise mechanism for KIT regulation by PKCθ remains unclear, PKCθ binds to KIT and KIT regulates phosphorylation of PKCθ (84). Drugs against PKCθ would be expected to have acceptable toxicity, and would not likely be affected by the presence of imatinibresistant KIT mutations.…”
Section: Strategies To Overcome And/or Prevent Resistancementioning
confidence: 99%
“…Primary PDGFRA mutations in the juxtamembrane domain (exon 12), the first tyrosine kinase domain (exon 14), and the activation loop (exon 18) are also associated with the pathogenesis of GISTs in approximately 5-7% of cases [Cassier et al 2012;Corless et al 2005]. Downstream PI3K/AKT and RAS/RAF/mitogen-activated protein kinase (MAPK) pathways are constitutively active in GIST models and cell lines in a KIT-dependent manner through direct interaction with signal intermediates PI3K and GRB2 [Duensing et al 2004;Zhu et al 2007]. In vitro pharmacological studies have corroborated the importance of these two signaling cascades in both imatinib-sensitive and imatinib-resistant GISTs [Bauer et al 2007].…”
Section: Molecular Biology Of Gistsmentioning
confidence: 99%